The effects of supplementary low-load blood flow restriction training on morphological and performance-based adaptations in team sport athletes - Scott, B. R.; Peiffer, J. J.; Goods, P. S. R. (The Journal of Strength and Conditioning Research, 2017)
Low-load resistance training with blood flow restriction (BFR) may be a method to enhance muscular development even in trained athletes. This study aimed to assess whether supplemental low-load BFR training can improve muscle size, strength, and physical performance characteristics in team sport athletes. Twenty-one semiprofessional Australian football athletes were assessed for 3-repetition maximum (3RM) and muscular endurance in the back squat, vastus lateralis muscle architecture, and performance in sprint and vertical jump tasks. Participants then undertook a 5-week training program, consisting of normal high-load resistance training supplemented by low-load squats with (LLBFR) or without (LL) BFR. Participants also performed regular conditioning and football training during this period. After the training intervention, participants again completed the pretraining testing battery. Squat 3RM and endurance increased from pretraining levels in both LL (3RM = 12.5% increase; endurance = 24.1% increase; p = 0.007) and LLBFR (3RM = 12.3% increase; endurance = 21.2% increase; p = 0.007) groups, though there were no between-group differences. No post-training changes were observed for muscle architecture, or performance in sprinting and jumping tasks. Although squat 3RM and endurance performance increased in both groups, adding BFR during supplemental exercise did not enhance these responses. Similarly, there were no large differences in the assessments of sprint, acceleration, and jumping performance between the groups after training. These findings suggest that although LLBFR did not negatively affect adaptive responses to resistance training, this training strategy may not provide added benefit for healthy Australian football athletes already undertaking a rigorous training schedule.